Impact of metformin on periodontal response to orthodontic forces in type 1 and 2 diabetic rats - Laura, Ever Elias Mena (2019)
Objectives: We studied the periodontal response to orthodontic forces in type 1 diabetic rats (T1D) treated with insulin and metformin and type 2 diabetic rats (T2D) treated exclusively with metformin (MET). Materials and methods: In article 1, T1D was induced by single injection of streptozotocin (STZ), whereas in article 2, T2D was induced by 90 days of high fat diet (HFD) with a single and low dose administration of STZ. In both articles 1 and 2 as soon as diabetes was induced in rats, an orthodontic appliance was installed to move the right upper first molar mesially for periods of 0, 3, 7, and 14 days. Samples were analyzed by micro-CT histomorphometry and immunohistochemistry for TRAP + cells. Results: Diabetic induction with STZ on the one hand, and HDF plus STZ on the other resulted in pathognomonic signs of T1D (hyperglycemia) and T2D (increase in body mass, insulin resistance, glucose intolerance and hyperglycemia), respectively. The addition of MET decreased blood glucose to values close to NG and better than insulin alone in T1D. In T2D, MET significantly reduced blood glucose, insulin tolerance and glucose tolerance. During orthodontic movement (OTM), T1D and T2D led to greater mesial movement, mesial inclination, mesial rotation (mesioversion), periodontal ligament spacing associated to a larger number of TRAP+ cells, and bone resorption surfaces (ORS) which were significantly reduced by MET on T2D and MET added to insulin on T1D. T2D presented maxillary osteoporosis or reduced BV / TV and BA / TA before OTM, but in T1D this occurred during OTM, however these effects were counteracted by MET. Yet, a different pattern of OTM occurs in T1D and T2D due to different bone density, and extrusion versus intrusion presented in T1D and T2D, respectively. Conclusion: The addition of metformin to insulin in T1D or single administration in T2D reduces the adverse effects on periodontal tissues during orthodontic movement in type 1 and 2 diabetic rats.